You may also like

problem icon

Roots and Coefficients

If xyz = 1 and x+y+z =1/x + 1/y + 1/z show that at least one of these numbers must be 1. Now for the complexity! When are the other numbers real and when are they complex?

problem icon

Three by One

There are many different methods to solve this geometrical problem - how many can you find?

problem icon

Target Six

Show that x = 1 is a solution of the equation x^(3/2) - 8x^(-3/2) = 7 and find all other solutions.

Sextet

Age 16 to 18 Challenge Level:

Oliver from Olchfa School and Simon from Elizabeth College, Guernsey both proved a general property of the sequence, namely that each term is the difference of the two previous terms. From this they found that the sequence is a repeating cycle of six values. You may like to consider more general sequences $a, b, b-a, ... $ with the property that each term is the difference of the two previous terms and investigate whether such sequences are always cyclical.

This is Oliver's solution:

Let $A_1 = x + {1\over x} = 1$ and note that $x$ has no real solutions. Let $A_n = x^n+ {1\over x^n}$.

We have $A_0 = 1 + 1 = 2$.

For $A_2 = x^2+ {1\over x^2}$, as $(x + {1\over x})^2 = x^2 + 2 + {1\over x^2}= 1$ so $A_2 = A_1 - A_0 = 1 - 2 = -1$.

For $A_3 = x^3+ {1\over x^3}$, since $A_2 = x^2 + {1\over x^2} = (x^2 + {1\over x^2})(x + {1\over x}) = x^3 + x + {1\over x} + {1\over x^3} = A_3 + A_1$, therefore $A_3 = A_2 - A_1 = -1 -1 = -2$.

In general $A_{n-1} = x^{n-1} + {1\over x^{n-1}} = (x^{n-1} + {1\over x^{n-1}})(x + {1\over x}) = x^n + x^{n-2} + {1\over x^n} + {1\over x^{n-2}} = A_n + A_{n-2}$, therefore $A_n = A_{n-1} - A_{n-2}$.

From $A_0=2$ and $A_1=1$ we can generate the whole sequence of $A_n$ as follows: 2, 1, -1, -2, -1, 1, 2, 1, -1, ... We can see that the sequence is a repeating pattern of 2, 1, -1, -2, -1, 1 for successive values of $n$ with a period of 6.

Rupert from Wales High School noted that:

$x^3= -1$ and hence that $x^4 = -x$, $x^5 = -x^2$ and $x^6 = -x^3 = 1$. If $x + {1\over x}=1$ then $x^2-x + 1 = 0$ and $x\neq -1$ so $(x+1)(x^2 - x +1)=x^3 +1 =0$. Hence $x$ is the cube root of $-1$ so $x^4 = -x$ and $x^7 = x$. From this it is easy to show that $x^n + {1\over x^n}$ takes the values 1, -1, -2, -1, 1, 2, 1, -1, .... cyclically.